Strategi Pencegahan Penyakit Kardiovaskular pada Lansia dengan Skrining Lemak Tubuh menggunakan Fat Caliper - Priyana, Andria; Santoso, Alexander Halim; Gunaidi, Farell Christian; Lucius, Steven Hizkia; Alifia, Khalisya (Jurnal Pengabdian West Science, 2025)
Abstract: Obesity is an increasing health problem among individuals of productive age and has a significant impact on the risk of chronic diseases. Early detection of obesity is essential to prevent metabolic and cardiovascular complications, particularly in vulnerable populations such as those residing in urban areas. This community service activity was conducted through nutritional status screening using Body Mass Index (BMI) and Waist-to-Hip Ratio (WHR) measurements among 107 productive-age participants in Tanjung Duren Village, West Jakarta. In addition to screening, participants received education on obesity risk factors and prevention strategies. The screening results revealed variations in nutritional status, with 66.36% of participants categorized as obese based on BMI, and 71.03% exhibiting high WHR, indicating central obesity. Anthropometric screening has proven to be effective in the early detection of obesity risk. The educational sessions played an important role in increasing participants' awareness of the importance of adopting a healthy lifestyle to prevent obesity-related complications. This activity successfully identified obesity risk within the community and enhanced knowledge on disease prevention. Routine early detection and educational programs are necessary to improve community quality of life and reduce the burden of obesity-related diseases.